Dziennik pisany noca, 1980-1983 - Herling-Grudzinski, Gustaw, 1919- (Paryz : Instytut Literacki, 1984)
Diaries of the Polish author covering 1980-1983.
Continues: Dziennik pisany noca, 1973-1979.
Keywords: Herling-Grudzinski, Gustaw, -- 1919-; Authors, Polish -- 20th century -- Biography